Stay awhile in my burrow! Interspecific associations of vertebrates to Indian crested porcupine burrows. Issue 4 (4th July 2019) - Mukherjee, Aditi; Pal, Arijit; Velankar, Avadhoot Dilip; Kumara, Honnavalli Nagaraj; Bhupathy, Subramanian
Abstract : The Indian crested porcupine, Hystrix indica, is a significant ecosystem engineer that builds extensive burrows in the semi-arid regions of north-west India. Many different animals use these burrows as temporary retreats or permanent shelters. Camera-traps were used to record 22 species using porcupine burrows, including 10 mammals, 8 birds, 3 reptiles, and 1 amphibian. In addition to birds foraging inside and around the entrance, the most common and persistent visitors were mongooses, rats, squirrels, hares, jungle cats, and small Indian civets. A bat species, Hipposideros sp. was found to be permanent occupants of porcupine burrows, while Indian rock pythons and jackals exhibited seasonal use. During winter, pythons basked outside the burrows and constricted their activities to the daytime. Conversely, porcupines are nocturnal and use deeper parts of their burrows than the pythons. Temporal usage patterns and spatial segregation allows for mutualistic behaviour between pythons and porcupines. Jackals were also found to use porcupine burrows during their summer breeding season, employing aggression to evict both porcupines and pythons. The study demonstrates a functional role for porcupines, which are capable of constructing "landmark" structures in the semi-arid regions of north-west India that support a range of micro-communities.